9514 1404 393
Answer:
f(g(x)) = -3x^2 -2x -3
Step-by-step explanation:
<u>Given</u>:
f(x) = -x-7
g(x) = 3x^2 +2x -4
<u>Find</u>:
f(g(x))
<u>Solution</u>:
Substitute per the function definitions.
f(g(x)) = f(3x^2 +2x -4) = -(3x^2 +2x -4) -7
f(g(x)) = -3x^2 -2x -3
Answer:44
Step-by-step explanation:
Answer:
x=10/27
Step-by-step explanation:
just add the E's on one side than move over the other E than move 14 to the 4 by minusing it
Answer:
16
Step-by-step explanation:
the two negatives cancel out so if you are subtracting -8 from 8 you would actually end up adding them.
hope it helps!